Table Banking and Women Economic Empowerment in Nakuru County, Kenya (American Journal of Youth and Women Empowerment, 2023)
This publication is part of a wider study which aims at evaluating Women Economic Empowerment programme, which is being implemented by the Women Empowerment Link (WEL) in several counties across Kenya, since 2015. In Nakuru the programme targeted grassroot women in table banking. To make the evaluation comprehensive in determining the level of women economic empowerment, this study adopted Kabeer’s (2005) theoretical framework for measuring women’s empowerment. The objective of the study was to establish the extent to which table banking had increased women economic empowerment in Nakuru County. Specifically, the study sought to assess the extent to which; the WEL’s project had enhanced women’s participation in county governance, women’s participation in the project had increased access to services and resources; and finally Identify success stories, lessons learnt and challenges that women in the project encountered. The study reached a total of 206 out of the 473 women who had been trained on basic financial literacy from 35 table banking groups. In each of the selected groups, three officials (the chairperson, secretary and the treasurer) and three members participated in the study. Key informants, 2 gender officers, 1 gender champion also participated. Data analysis revealed that 80% of the women were business owners, 10.21% were employed while 6.6% were domestic workers. The study’s findings revealed that WEL’s programme on Strengthening Inclusive Leadership had mixed results in enhancing participation of women in leadership and governance. Only half of the women at 49.51% had offered themselves for leadership and governance positions yet their capacities and availability to participate in leadership and governance were rated very high. The study also found that women’s participation in the WEL’s project had increased access to services, resources and women’s participation in governance opportunities to a large extent. Finally, the study appreciated that the WEL project in Nakuru targeted most vulnerable, low income i.e., economically vulnerable grassroots women. Among the obstacles found to be hindering Women Economic Empowerment were poverty, high level of illiteracy and lack of information. Among other recommendations, women requested additional seed capital from either WEL or County Government to increase their borrowing power within their groups and expand adult literacy programme by the County Government. The study also recommended concerted campaign to include more women in leadership and governance.